Enrichment of maize and triticale bran with recombinant Aspergillus tubingensis ferulic acid esterase - Zwane, Eunice N. (J Food Sci Technol, 2017)
Ferulic acid is a natural antioxidant found in various plants and serves as a precursor for various fine chemicals, including the flavouring agent vanillin. However, expensive extraction methods have limited the commercial application of ferulic acid, in particular for the enrichment of food substrates. A recombinant Aspergillus tubingensis ferulic acid esterase Type A (FAEA) was expressed in Aspergillus niger D15#26 and purified with anion-exchange chromatography (3487 U/mg, K (m) = 0.43 mM, K (cat) = 0.48/min on methyl ferulate). The 36-kDa AtFAEA protein showed maximum ferulic acid esterase activity at 50 °C and pH 6, suggesting potential application in industrial processes. A crude AtFAEA preparation extracted 26.56 and 8.86 mg/g ferulic acid from maize bran and triticale bran, respectively, and also significantly increased the levels of p-coumaric and caffeic acid from triticale bran. The cost-effective production of AtFAEA could therefore allow for the enrichment of brans generally used as food and fodder, or for the production of fine chemicals (such as ferulic and p-coumaric acid) from plant substrates. The potential for larger-scale production of AtFAEA was demonstrated with the A. niger D15[AtfaeA] strain yielding a higher enzyme activity (185.14 vs. 83.48 U/ml) and volumetric productivity (3.86 vs. 1.74 U/ml/h) in fed-batch than batch fermentation.